A Dermatoglyphic Study: Association of Fingerprint Patterns Among ABO Blood Groups - Tri Panjiasih Susmiarsih; M. Samsul Mustofa; Mirfat Mirfat (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Fingerprints are probably the most common biometric technique used in personal identification. The potential of fingerprints to determine sex and human identification has been well exhibited. However, very few studies have been conducted correlating finger prints with blood groups. The aim of this study was to investigate the distribution of fingerprint patterns based on ABO blood groups. The total sample consisted of 302 medical students of YARSI University Jakarta comprising of 187 females and 115 males. The fingerprint patterns were classified into arches, loops (ulnar and radial), whorls. counted and comprised triradius and total ridge count. The data analysis used Chi Square and Student-T test.The study results indicated that there were fourth especially pattern type. Significantly (p0.05), frequency of loop types (60.36%) was highest in B blood, whorl type was highest in O blood (40.45%) and arches in AB blood was higher (5.12%) as compared to other groups. Dankmeijer indices of O and AB blood were 3.78 and 11.34, respectively. There were indicated significantly (p0.05) difference of average ridge count total among ABO blood groups. This study implied an association between dermatoglyphics and blood groups.How to CiteSusmiarsih, T. P., Mustofa, M. S., Mirfat, M. (2016). A Dermatoglyphic Study: Association of Fingerprint Patterns Among ABO Blood Groups. Biosaintifika: Journal of Biology Biology Education, 8(3), 294-300.